Rehabilitation Strategy for Water Networks using Risk-Performance Based Decision Making: - Bubtien, Abdelwahab M. (Conference On Engineering Science and Technology, 2021)
A proactive rehabilitation strategy is introduced based on optimizing scheduling of individual pipes for replacement, considering minimum costs and maximum performance. Performance indicators are used to identify level of a system performance that reveals severity of breakage consequences (risks). Risks are estimated by using breakage rate and consequences of the failure. In this article the performance indicators used are pressure and connectivity to identify hydraulic capacity and reliability of the system performance. A rehabilitation strategy is applied when performance indicators fall below predefined threshold, the present paper describes such an approach, which permits a judicious choice of solution along a trade-off curve between performance and cost. This strategy was applied on a real-world water distribution system, Benghazi city in Libya, the required rehabilitation is determined for the next five years (2018 to 2025) in addition, significance improvement in hydraulic performance are observed too.
Keywords: Breakage rate; Rehabilitation; Replacement; Risk performance Pipe; Reliability